2021
DOI: 10.3390/jcm10194468
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Alcohol Use during the COVID-19 Pandemic among Young Adults: The Prospective Effect of Anxiety and Depression

Abstract: Health measures instantiated to reduce the spread of COVID-19 have imposed significant constraints for the population and impacted on drinking habits and mental health. This study longitudinally compared changes in alcohol consumption before and after the COVID-19 outbreak and the impact of sociodemographic and mental health variables on such changes among a community sample of young adults. Data were collected in the context of a larger, ongoing longitudinal study. The sample consisted of 305 young adults fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 67 publications
0
5
0
2
Order By: Relevance
“…Nevertheless, studies have shown that the COVID-19 pandemic negatively impacted young adults’ psychological well-being and mental health [ 6 , 7 , 8 ], and this may have led some youths to use substances (e.g., alcohol) to alleviate distress and negative feelings associated with the dramatic situation. For instance, Vera et al [ 22 ] documented that young people with higher levels of depression were more resistant to decreasing their alcohol consumption during the pandemic relative to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, studies have shown that the COVID-19 pandemic negatively impacted young adults’ psychological well-being and mental health [ 6 , 7 , 8 ], and this may have led some youths to use substances (e.g., alcohol) to alleviate distress and negative feelings associated with the dramatic situation. For instance, Vera et al [ 22 ] documented that young people with higher levels of depression were more resistant to decreasing their alcohol consumption during the pandemic relative to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol can be used as a coping strategy for depressive thoughts (i.e., self-medication theory) [ 67 ]. For example, a longitudinal study documented that young adults with more depressive symptoms before the pandemic were more resistant to reduce their frequency of alcohol use following the COVID-19 pandemic [ 68 ]. Conversely, higher alcohol consumption may also contribute to increases in risk of depressive symptoms [ 69 ], although this risk might be more likely to be experienced by those who had problematic use of alcohol before the pandemic (e.g., heavy drinking behaviors).…”
Section: Discussionmentioning
confidence: 99%
“…Egyes kutatások szerint a pandémiás korlátozások során az egyetemi hallgatók körében megnőtt az alkoholfogyasztás, a dohányzás, valamint a kávé fogyasztásának gyakorisága (Al Miskry, Hamid & Darweesh, 2020;Charles, Strong, Burns, Bullerjahn & Serafine, 2021). Más vizsgálatok pedig épp ennek az ellenkezőjét sugallják, vagyis, hogy a pandémiás időszakban jelentősen csökkent a különböző pszichoaktív anyagok használata a fiatalok körében (Fruehwirth, Gorman & Perreira, 2021;Tavolacci et al, 2021;Vera et al, 2021).…”
Section: Bevezetésunclassified
“…Egyes nemzetközi adatok azt mutatják, hogy a COVID-19-járvány miatt bevezetett intézkedéseket követően az egyetemi hallgatók körében megnőtt az alkoholfogyasztás, a dohányzás, valamint a kávé fogyasztásának gyakorisága (Al Miskry, Hamid & Darweesh, 2020;Charles et al, 2021;Lechner, Laurene, Patel, Anderson, Grega & Kenne, 2021). Más kutatások eredményei ugyanakkor azt igazolták, hogy a pandémia ideje alatt az egyetemisták többségénél az alkoholfogyasztás mértéke nem változott (Kohls, Baldofski, Moeller, Klemm & Rummel-Kluge, 2021) vagy éppen hogy csökkent (Bollen et al, 2021;Vera et al, 2021) a korábbi fogyasztás mértékéhez képest. Egy hazai nagymintás vizsgálat (n=3353) eredményei is azt igazolták, hogy a magyar egyetemisták körében mind a dohányzás (24,2% vs. 20,3%), mind pedig a nagy ivás (45% vs. 20,5%) prevalenciája csökkent a koronavírus-járvány alatt az azt megelőző időszakhoz képest (Arnold, Elekes & Bencsik, 2020).…”
Section: Következtetésekunclassified